Managing multiple myeloma in the over 70s: A review. Issue 2 (February 2015) - King, Andrew J; Gooding, Sarah; Ramasamy, Karthik
Highlights The management of myeloma in the over 70s differs from younger patients: treatment goals vary and underlying co-morbidities have to be taken into account. Age alone should not be a barrier to intensive treatment. Comprehensive geriatric assessment is indicated in the over 70s.